The Effect of Government Spending in the Education and Health Sectors on the Human Development Index (HDI) In Indonesia: An Ardl Approach - Sembiring, Pebry Yola Sari Br.; Hidayat, Paidi; Syafii, M. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of government spending on education and health on the Human Development Index (HDI) in Indonesia by including population size, open unemployment rate, and gender ratio as control variables. The analysis method used is Autoregressive Distributed Lag (ARDL) using time series data for the period 1990–2023 obtained from the Central Statistics Agency (BPS) and the Ministry of Finance of the Republic of Indonesia. The results show that in the short term, education expenditure has a positive and significant effect on the HDI, while health expenditure and population size have a negative and significant effect. Meanwhile, the open unemployment rate and gender ratio have a negative but insignificant effect. In the long term, education expenditure has a positive but insignificant effect, while health expenditure, population size, and gender ratio have a negative and significant effect on HDI. These findings indicate that HDI improvement is not solely determined by the amount of government spending, but rather by the effectiveness of budget management, population growth control, expansion of employment opportunities, and improvement of gender equality as prerequisites for sustainable human development.